PKM Usaha Rumahan Pembuatan Jamu Tradisionil Sebagai Upaya Peningkatan Kualitas Produk - Mundari, Siti; Herlina, Herlina (PROSIDING SEMINAR NASIONAL PENGABDIAN KEPADA MASYARAKAT, 2023)
The home business of making traditional herbal medicine carried out by Mrs. Khasi'ah as a Community Service Partner whose address is Jalan Penjaringan 3 no.10 Rungkut Surabaya is a business that was founded 40 years ago. Mrs. Khasia'ah is an elderly widow aged 70 years who is able to live independently by making traditional herbal medicine (beras kencur, sinom, kunir asam, cabe puyang, suruh kunci, sambiloto, mengkudu laos) to be marketed around the village every day. The problem found based on observations from Wak Si''s traditional herbal medicine business was that the equipment for grinding ingredients (kunir, jahe, kunci, kencur, etc.) still used a mashing tool in the form of an ancient mortar which caused the process of making herbal medicine to take a long time. Apart from that, the process of making herbal medicine is that when it is finished boiling, it is placed in a bucket made of old plastic (not suitable from a health perspective). Problems also occur when selling around the village, namely the carts used to sell herbal medicine are rotten and the bottles used for herbal medicine are used mineral water bottles which should not be used again. The solutions offered to overcome Mitra's problems are: procuring a blender to mash the ingredients so that the process of making herbal medicine can be done in a shorter time, procuring an aluminum pan to hold the herbal medicine that has been boiled so that it is suitable from a health perspective, making a cart because the existing cart is already rotting, it's time to replace it. and providing drinking containers as a place for herbal medicine to replace used mineral water bottles so that they are suitable as drink containers. The results obtained from this community service program are that the process of refining herbal medicine raw materials can be done more quickly, the process of making herbal medicine is hygienic, adequate carts for herbal medicine and bottles for storing herbal medicine are suitable.